(untitled) (LACCEI, 2024)
Contamination by heavy metal(loid)s is one of the most evident problems in the areas of mining influence. In Ecuador, this problem has persisted for several years in artisanal and small-scale mining (ASM) districts such as Ponce Enriquez. To evaluate the contamination and propose contaminant mitigation strategies, this study was developed located in the orchards of the Association of mineral collectors ’Unión y Progreso’ close to the La Independencia community. For this purpose, water, soil, and plant samples from the crop area and its surroundings were analyzed. The heavy metal(loid) contamination indices calculated were the metal index (IM) for water, pollution load index (ICC) and ecological risk (RI) with soil data, and bioaccumulation index (IBC) in vegetables. The results showed that the irrigation water was not contaminated, being identified as very pure according to the IM in 100% of the samples. In the soil, it was determined that the highest contaminant load of As, Cr, Cu, Ni, Pb, and Zn was in the extreme northeast of the study area. In addition, according to the ICC, light contamination was indicated in 50% of the samples and moderate contamination in the rest. The RI values ​​varied in a range from moderate to very high, with As and Cd being the elements with the greatest contribution to the degree of soil contamination. According to the IBC, the sample of chives and turnips were identified as Cd accumulators, with values ​​of 1.02 and 1.53 respectively. With these results, it was determined that the soil presented the greatest problem for the contamination of the area and even for food safety. From this, strategies for the mitigation of contaminants were proposed that included the application of alternative methods such as hydroponics for the cultivation of vegetables, and methods for soil remediation were recommended. This information could serve as an input in the management and reduction of pollution, as well as in the protection of the health of the inhabitants.